The Influence of Cognitive Psychology on Student Responses in Mathematics Learning - Kamid; Rohati; Ramalisa, Yelli; Oktavia, Sri Wina (Universitas Pendidikan Ganesha, 2024)
There is a significant gap between cognitive psychology theory and learning practices in many educational institutions. As a result, many students do not fully benefit from approaches designed to improve comprehension and retention. This research aims to analyze the influence of cognitive psychology on students' responses to learning mathematics. The research approach used is a quantitative approach with comparative methodology. In this research, a purposive sampling technique was chosen to random sampling. The research sample consisted of 120 class VII students from two schools. The sampling technique used was random sampling. This research sample was taken from four class VII, with a total of 30 research subjects. Data was collected using instruments in the form of a cognitive psychology questionnaire and a questionnaire on student responses to mathematics learning as measured by a Likert scale. Quantitative data analysis was carried out using data processing software with comparison tests and influence tests. The research results showed that there were significant differences in aspects of cognitive psychology between the two groups studied. Apart from that, the research results also indicate that cognitive psychology has a significant influence on students' responses to mathematics learning. By understanding the influence of cognitive psychology on student responses, educators can develop more effective teaching strategies that can increase student motivation and learning achievement.